Decision-Making Policies of Leaders within Islamic Boarding School’s Institute to Improve Formal Education Managerial’s Quality - Syarif Ali AlQadrie (JIEMAN: Journal of Islamic Educational Management, 2022)
The rationale of the research context in this study is mainly related to the fact that there is such a significant impact of the decision-making procedure taken by leaders in Islamic Boarding School, mostly known as pesantren, to improve the quality of managerial activities in formal educational institutions. Islamic boarding school institutes that oversee formal educational institutions have different strategies and decision-making with targeted goals and distinctive considerations in regulating the decisions to be reached. This study focuses on the design, implementation, and evaluation of decision-making. This study used a descriptive qualitative approach. The data were collected through observation, documentation, and interviews. The data analysis used is data reduction, data presentation, and data verification. The results showed that: first, the decision-making design consisted of steps like forming a team, identifying needs analysis, program designing, employing program socialization, and undergoing process evaluation, while the focus of the decision-making design was to improve the quality of management. Second, the implementation of decision-making procedures from the leaders can be seen in improving the quality of human resources, where they fixed and highlighted this particular aspect as they are directly related to the quality of school management. Third, the leaders' evaluation process was done directly and indirectly through some discussion. The evaluation standard used is the evaluation undergoes the process within the decision is implemented and at the impact of the decision to measure how significant it is.  Penelitian ini dilatarbelakangi karena adanya pengambilan keputusan pimpinan yayasan yang dalam kaitannya meningkatkan mutu pengelolaan di lembaga pendidikan formal. Yayasan yang menaungi lembaga pendidikan formal memiliki strategi dan pengambilan keputusan yang berbeda dengan tujuan yang terarah dan adanya sebuah pertimbangan khusus dalam menetapkan keputusan yang akan direalisasikan. Kajian ini difokuskan pada desain, implementasi dan evaluasi pengambilan keputusan. Pendekatan yang digunakan dalam penelitian ini pendekatan kualitatif deskriptif. Untuk mengumpulkan data digunakan beberapa metode yaitu, observasi, dokumentasi dan wawancara. Sedangkan analisis datanya yakni reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan bahwa: pertama, desain pengambilan keputusan terdiri dari langkah-langkah berupa pembentukan tim, analisis kebutuhan, rancangan program, sosialisasi program, evaluasi proses, sedangkan bentuk desain pengambilan keputusan pimpinan yayasan dalam meningkatkan mutu pengelolaan. Kedua, pada Implementasi pengambilan keputusan dari pimpinan yayasan terlihat pada peningkatan mutu SDM, dimana pimpinan yayasan membenahi dan fokus pada SDM. Karena bagi pimpinan yayasan hal yang terkait langsung dengan pengelolaan sekolah yakni terletak pada SDM yang berkualitas. Ketiga, evaluasi dari pimpinan yayasan yakni secara langsung dan tidak langsung dan selalu dimusyawarahkan.  Standar evaluasi yang digunakan yakni pada evaluasi ketika dilakukan saat proses maupun akhir dari keputusan tersebut dan mengukur seberapa jauh pengambilan keputusan tersebut